FIRE AWARENESS AND PUBLIC PREFERENCES IN ENHANCING RESIDENTIAL FIRE SAFETY SYSTEMS IN DENSE URBAN SETTLEMENTS IN INDONESIA - Anes, Anggun V. M.; Larasati, Dewi; Tambunan, Lily (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2026)
Ensuring fire safety in dense residential areas is a major concern in urban disaster mitigation. The high incidence of fires and their impacts, including fatalities, economic losses, and social disruption, underscore the need to evaluate existing prevention systems. Aims: This study examines the relationship between fire alarm availability, evacuation training participation, and community preferences for improving fire safety measures. Methodology and results: A mixed-methods approach was used, integrating quantitative chi-square analysis with qualitative grounded theory. Quantitative data were obtained from a structured survey of 111-respondents, and qualitative data were derived from open-ended responses analyzed through open, axial, and selective coding. The results revealed a significant association between fire alarm availability and preferences for strengthening early warning systems (p = 0.0025). Participation in evacuation training was also significantly related to recommendations for improving evacuation facilities and procedures (p = 0.0064). Qualitative findings show that trained individuals prioritize accessible evacuation routes and routine simulation exercises. Conclusion, significance, and impact study: The study proposes three strategies: (1) improving affordability and access to fire alarm systems, (2) increasing community-based evacuation training, and (3) designing evacuation routes adapted to dense settlement conditions. These measures are expected to enhance fire safety and strengthen community resilience in high-risk residential areas.